Determinants and Capital Market Consequences of Net Zero Targets - Samuel Jonas Kaltenhauser (Junior Management Science (JUMS), 2023)
Net zero emission - Recently, a frequently cited climate target in the corporate sector. Meeting public pressure, gaining reputation, and optimizing resources are among the core motivations to pursue such a target. Opposed to this stand a high level of complexity and costs. Thus, from an investor's view, an assessment of profitability can be mixed. Moreover, the risk of greenwashing renders it challenging to assess the sincerity of such a target. The goal of this paper is twofold. First, I analyze which firm and industry determinants might explain net zero target announcements by Russell 1000 listed companies. Second, I measure the capital market reaction by means of an event study and examine the influence of target characteristics defined within a purpose-developed ESG score. The results reveal a significant correlation between a variety of determinants and a net zero target announcement (e.g., industry profile, firm size) and show a significant negative capital market response irrespective of a target's individual attributes. The latter result indicates a general skepticism of investors towards net zero pledges. I conclude that enhanced external enforcement options and greater transparency by companies regarding their actual target realization plans may reduce this skepticism.
Keywords: 650; Net zero; Carbon neutral; Climate target; Determinants; Capital market consequences